Chasing Helicity - Zee, Ginger (Disney-Hyperion, 2018)
Thirteen-year-old Helicity, not a victim of a horrific tornado but a survivor, connects with a local meteorologist and other stormchasers who support her plan to become one of them.--Provided by Publisher.